Osteoarthritis: State-of-the—Art - Vinall, Phil (MD Conference Express, 2007)
This article presents an overview of some of the work that has been done to identify prognostic indicators for progression of hip and knee arthritis and about the markers of osteoarthritis (OA). Other topics discussed include an analysis of the GARP Study, radiographic views and scoring methods available to identify structural damage in knee OA, and the future of OA treatment.